A country called prison: mass incarceration and the making of a new nation - Looman, Mary D. (Oxford University Press, 2015)
Machine generated contents note: -- Chapter 1: Introduction to a Country Called Prison -- Chapter 2: What Makes Prisons A Country? -- Chapter 3: Who Are the People of a Country Called Prison -- Chapter 4: Life in a Country Called Prison -- Chapter 5: Visiting America From a Country Called Prison -- Chapter 6: Emigrating From a Country Called Prison -- Chapter 7: Assimilating a Country Called Prison -- Appendix: Summary of Proposals